A pragmatic approach to the contrastive analysis of a literary work and two of its translations - Mur Dueñas, María Pilar (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2004)
There are two levels at which a pragmatic analysis can be carried out in relation to a literary work: the level of the narrative and the level of the text-production and reception. If the pragmatic analysis of a literary work is to be undertaken from a contrastive point of view, the picture becomes more complex, especially, if as in this case- the original literary text and the target texts are historically distant. The pragmatic analysis of Henry James’s Daisy Miller and two of its contemporary translations into Spanish that I intend to pursue here will be carried out in a contrastive way at the level of the narrative; the translated pragmatic actions in the narrative will be assessed in terms of the target readers’ new context of reception. The aim is to see whether and how the original writer’s intended meaning and interpretation has been kept in the target texts and if the pragmatic effect that these texts are likely to cause on the Spanish readership can be considered similar to the effect the source text is likely to provoke on contemporary source readers.